COMPARISON OF PROTEIN DETERMINATION METHODS IN C-PHYCOCYANIN FRACTION FOR THE DEVELOPMENT OF PROTEASE ACTIVITY DETERMINATION KIT - Daniel Irsan Pasaribu, Kevin
C-Phycocyanin (CPC) is one type of phycobiliprotein found in Spirulina platensis and has numerous benefits. In previous research, CPC has been developed as a substrate for determining pancreatic protease activity. The aim of this study is to determine the appropriate method for protein content determination in the developed CPC fraction. Protein content is one of the parameters that need to be determined to ensure the quality of the CPC fraction. The research was conducted in several stages, including the preparation of the CPC fraction, selection of the protein determination method, verification of the chosen method, and application of the selected method. The obtained CPC fraction has blue luminescent characteristics, with a spectrum peak at a wavelength of 620 nm, CPC content of 0.117 mg/mL, and purity of 1.063. The results of the method selection indicate that the most suitable method is the Bradford method. The verification of the Bradford method shows a correlation coefficient value of 0.9981, limit of detection 0.044 mg/mL limit of quantification 0.147 mg/mL, a recovery percentage range of 97.313- 100.228%, and %RSD of 1.71%. The application of the Bradford method to the CPC fraction sample shows a concentration of 0.151 mg/mL